2009 10th International Conference on Document Analysis and Recognition 2009
DOI: 10.1109/icdar.2009.80
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Handwritten Farsi Numerals Recognition Using Sparse and Over-Complete Representations

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We have used Stochastic Gradient Approach as it avoids being stuck in poor local minima which is highly likely due to the non linear nature of the error surface. A simplified CNN was presented in [25] which we have used for our work instead of using the rather complicated LeNet-5 [26]. The model has five layers.…”
Section: Artificial Immune Systems (Ais): Ais Use Clonal Selection An...mentioning
confidence: 99%
“…We have used Stochastic Gradient Approach as it avoids being stuck in poor local minima which is highly likely due to the non linear nature of the error surface. A simplified CNN was presented in [25] which we have used for our work instead of using the rather complicated LeNet-5 [26]. The model has five layers.…”
Section: Artificial Immune Systems (Ais): Ais Use Clonal Selection An...mentioning
confidence: 99%
“…In contrast, very little research had reported the recognition of Persian (Arabic) handwritten digits (Liu et al, 2009;Pan et al, 2009;Borji et al, 2008;Suen et al, 2006;Soltanzadeh and Rahmati, 2004;Amin, 1998). However, today research on Farsi (Persian) scripts and *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…This article does not use complex CNN structure [6], but refer to simplify the structure of the CNN [7]. Our CNN structure is shown in Figure 1.There are seven layers.…”
Section: Cnnmentioning
confidence: 99%